Fixture for dental implant dynamic fatigue test - HUANG YUMEI; TIAN JIMEI; LU LIMING; DENG YANNAN (2020)
The invention provides a fixture for a dental implant dynamic fatigue test. The fixture comprises a bottom plate, a horizontal movement adjusting device arranged on the bottom plate, an angle adjusting device, a rigid cylinder, a graphene heating film container, a mounting sleeve and a PLC controller, wherein the angle adjusting device is arranged on the horizontal movement adjusting device and includes a first horizontal plate; the bottom of the rigid cylinder is welded to a first horizontal plate; the graphene heating film container is arranged outside the rigid cylinder in a sleeving manner; the mounting sleeve sleeves the middle of the rigid cylinder from a top inclined surface of the top of the rigid cylinder, an external thread of the mounting sleeve can be screwed into an internal thread in the middle of the top inclined surface of the rigid cylinder, and a center hole is arranged in the mounting sleeve to fix a dental implant sample; and the PLC controller is connected with thegraphene heating film co